Solar Light-Induced Photoelectrochemical H2 Generation Over Hierarchical TiO2 Nanotube Arrays Decorated with CdS Nanoparticles - Raza, Waseem; Tesler, Alexander; Mazare, Anca Valentina; Schmuki, Patrik (Journal of The Electrochemical Society, 2024)
The process of converting solar energy into chemical energy through photoelectrochemical (PEC) water splitting holds significant promise for hydrogen and oxygen gas production. In the current study, we have demonstrated the feasibility of designing a high-performance heterojunction photoanode in a scalable manner. This photoanode sensitizes visible light active CdS onto hierarchical TiO2 nanotubes (TNT), thereby enhancing H2 generation. To achieve this, we initially employed an electrochemical anodization technique to fabricate vertically aligned self-organized TNT on a titanium (Ti) substrate. Subsequently, we designed a hierarchical structure for TNT by uniformly decorating them with TiO2 nanoparticles (NPs), thus amplifying the available surface area. By employing the sequential ionic layer adsorption and reaction (SILAR) technique, we establish visible light sensitization. The resulting decorated hierarchical TNT photoanode demonstrates an enhanced photocurrent of 2.60 mA cm−2 under AM 1.5 G simulated solar light, surpassing the performance of hierarchical TNT, and most importantly classic CdS/TNT structures by 17-fold, and 1.6-fold, respectively. Moreover, the developed photoanodes achieved photoconversion efficiency with an applied bias (ABPE) of 2.48%. Thus, this work shows that a hierarchical scaffold can be exploited to achieve enhanced activity in photoelectrochemical H2 generation.
CRIS-Team Scopus Importer:2024-07-19
Keywords: CdS; Heterojunction; Hierarchical Structure; Photoelectrochemical Water Splitting; TiO